IL28B (IFNL3) rs12979860 predicts response to interferon-α2a plus ribavirin in Pakistani adults with chronic hepatitis C: A longitudinal cohort study - Khan, Naimat Ullah; Shah, Syed Hasnain Ali; Altaf, Shandana; Anwar, Summayya; Khawaja, Tariq Mahfooz; Khan, Imran (International Journal of Pathology, 2025)
Background: Chronic hepatitis C virus (HCV) remains highly prevalent in Pakistan, with genotype 3 predominance. Before direct-acting antivirals (DAAs), interferon-α (IFN) plus ribavirin (RBV) yielded variable sustained virologic response (SVR). Host variants near IL28B (IFNL3), particularly rs12979860, have been linked to IFN responsiveness and spontaneous clearance. This study evaluates whether IL28B rs12979860 predicts SVR to IFN-α2a/RBV in Pakistani adults and to describe baseline viral-load strata and circulating genotypes.Methods: We conducted a longitudinal cohort in Khushal Medical Center (KMC) Peshawar (N=165). Adult’s anti-HCV–positive by third-generation ELISA started IFN-α2a thrice weekly plus weight-based RBV for 24–48 weeks. Baseline demographics, HCV RNA categories, and viral genotypes were recorded; IL28B rs12979860 was genotyped from whole blood. Virologic endpoints were Rapid viral response (RVR) (week 4), Early virological response (EVR) (week 12), and SVR (undetectable HCV RNA 24 weeks post-therapy). Associations were summarized as odds ratios (OR) with 95% CIs.Results: Overall SVR was 51.5% (85/165). Baseline RNA was <600,000 IU/mL in 81.8%, 600,000–800,000 in 2.4%, and >800,000 in 15.7%; all SVR events occurred in the <600,000 IU/mL group. Genotypes were dominated by 3a (45%) and 3b (19%) with smaller contributions from 2a (13%), 1a (6%), 2b (5%); 4a/5a/6a were rare; ~10% were untypeable. rs12979860 distributions differed by outcome: responders (n=84) CC 45, CT 32, TT 7; non-responders (n=80) CC 21, CT 26, TT 33. CC vs TT: OR 10.10 (95% CI 3.84–26.55); CC vs CT+TT: OR 3.24 (95% CI 1.68–6.25). EVR tracked positively with SVR.Conclusions: In a genotype-3–predominant Pakistani cohort, rs12979860-CC strongly predicted SVR to IFN-α2a/RBV (CC>CT>TT). These data provide population-specific pharmacogenomic evidence and a historical benchmark for Pakistan.